DCRY is a Drosophila photoreceptor protein implicated in light entrainment of circadian rhythm. - Ishikawa, T.; Matsumoto, A.; Kato, T.; Togashi, S.; Ryo, H.; Ikenaga, M.; Todo, T.; Ueda, R.; Tanimura, T. (Genes to cells : devoted to molecular & cellular mechanisms, 1999)
Light is the major environmental signal for the entrainment of circadian rhythms. In Drosophila melanogaster, the period(per) and timeless (tim) genes are required for circadian behavioural rhythms and their expression levels undergo circadian fluctuations. Light signals can entrain these rhythms by shifting their phases. However, little is known about the molecular mechanism for the perception and transduction of the light signal. The members of the photolyase/cryptochrome family contain flavin adenine dinucleotide (FAD) as chromophore and are involved in two diverse functions, DNA repair and photoreception of environmental light signals.We report the cloning of a new member of this family, dcry, from Drosophila. Northern blot analysis shows that this gene is expressed in various tissues. The dcry mRNA is expressed in a circadian manner in adult heads, while such rhythmic fluctuation is abolished in the clock-defective per0 and tim0 mutants. The circadian expression is dampened down in constant darkness. The over-expression of the dcry gene alters the light-induced phase delay in the locomotor activity rhythms of flies.These results suggest that DCRY is a circadian photoreceptor and that its expression is regulated by circadian clock genes.